The consistency and efficacy of optical coherence tomography for the evaluation of ocular torsion angle in children - Liu, Rongjun; Zhao, Jingjing; Yu, Kaili; Zhu, Dehai (Frontiers in Pediatrics, 2025)
PurposeTo explore the consistency and efficacy of optical coherence tomography (OCT) for the evaluation of ocular torsion angle compared to fundus photography in children.MethodPatients who had undergone fundus photography and OCT within 1 day were included in this study. The fundus photographs were taken using a fundus camera and then imported into the Adobe Photoshop 2021 software. The fovea-disc angle (FDA) was calculated manually. OCT was used to automatically detect the centers of the optic disc and fovea, and the software then calculated the FDA on the same device. The means and ranges of variables were calculated in this study. Group differences were assessed using the paired t-test. Statistical significance was determined when P-values were <0.05. Bland–Altman plots were constructed to verify the agreement of the FDAs measured by fundus photography and OCT respectively.ResultsA total of 100 patients were included and the objective measurements of the ocular torsion angles via OCT and fundus photography were similar. The mean FDA of 32 patients aged 2–6 years old was −7.84 ± 4.67° via fundus photography and −6.71 ± 6.19° via OCT. The mean FDA of 68 patients aged 6–18 years old was −8.47 ± 5.22° via fundus photography and −8.97 ± 5.41° via OCT. According to the receiver operational characteristic (ROC) curves of the FDA for diagnosing ocular extorsion, the area under the ROC curve was greatest for OCT (0.943, 95% CI: 0.902–0.984), followed by fundus photography (0.92, 95% CI: 0.86–0.979). With the Youden method, the optimal cut-off point for diagnosing ocular extorsion with OCT was −6.35°. OCT demonstrated a sensitivity of 100% and a specificity of 49.2%. Furthermore, the optimal cut-off point for diagnosing ocular extorsion with fundus photography was −6.5°.ConclusionThe comparison of FDAs showed good agreement between fundus photography and OCT. Thus, OCT can evaluate ocular torsion angle effectively in children.